The effects of nicotine on foetal loss, postnatal growth and plasma oestrogen and progesterone levels in rats / Siti Norashikin Mohd Tambeh, Sumitabha Ghosh and Mohd Hamim Rajikin. - Mohd Tambeh, Siti Norashikin; Ghosh, Sumitabha; Rajikin, Mohd Hamim (Universiti Teknologi MARA Cawangan Selangor, 2019)
The present study aims to investigate the effects of nicotine on foetal loss, postnatal growth and corresponding levels of oestrogen and progesterone in pregnant rats. Methods: Subcutaneous injection of nicotine tartrate (7.5 mg/kg/day) was administered to groups of pregnant rats; with treatment scheduled from day 1 through day 5, day 5 through day 9 or day 1 through day 9 of pregnancy. On day 10 of pregnancy, laparotomy was performed to count the number of blastocyst implantation sites. During parturition, the number of viable pups was recounted and statistically compared with the controls. One group of rats which received nicotine from day 1 through day 9 of pregnancy was sacrificed on day 16 of pregnancy, and circulating levels of oestrogen and progesterone were measured. Upon delivery, the birth weight of the pups was measured, and their weights were recorded until weaning. Results: There was a significant increase in foetal loss particularly in rats which received nicotine from day 5 through day 9 and from day 1 through day 9 of pregnancy. There was also significantly lower birth weight of pups in all groups; however, this pattern did not continue until weaning. Plasma oestrogen level was significantly elevated with a significant decrease in the plasma progesterone level. Conclusions: Nicotine administration during pregnancy showed an increase in foetal loss with a corresponding increase in oestrogen and decrease in progesterone levels. Although the birth weight of the pups was low, there was catch-up growth in the pups.